Peran Layanan BK Dalam Membantu Siswa Belajar di Masa Pandemi Covid-19 - Ade Chita Putri Harahap; Siti Rahmadanti Siregar; Wirda Selvya Tambunan; Yolanda Putri Dalimunthe; Yunita Arbaini Hutabarat (El-Mujtama: Jurnal Pengabdian Masyarakat, 2023)
Currently the whole world is in the midst of the Covid-19 Pandemic, and there are many changes in lifestyle, especially in the world of education. There are many aspects of change in education. Teachers are required to modify learning methods to adapt to current circumstances. Moreover, the guidance and counseling teacher is famous for the up-to-date teacher regarding information that is currently viral. With the Covid-19 pandemic situation, the implementation of guidance and counseling services in schools is carried out online. This is in accordance with the Circular of the Minister of Education and Culture Number 4 of 2020 with the term learning from home. To realize guidance and counseling services during the COVID-19 pandemic, BK teachers are required to use technology in carrying out their roles to carry out various BK services according to student needs. BK teachers can use a variety of media and communication platforms that are familiar to students. Because of this, guidance and counseling teachers make full efforts to learn how to make guidance and counseling services using application technology and social media that can be used to provide guidance and counseling services. The role of the guidance and counseling teacher must also think about how to continue to carry out various types of guidance and counseling services in order to remain effective according to the needs of students with limited direct interaction but by doing it online. Keywords: counseling teacher, learning method, student